Evaluasi Perilaku Kekerasan Narapidana oleh Petugas Pemasyarakatan di Lembaga Pemasyarakatan: Evaluation of Violent Behavior Prisoners by Correctional Officers at Correctional Institutions - Syahrial Yuska; Muhammad Ali Equatora; Mitro Subroto; Imaduddin Hamzah (Society, 2022)
There have been several violent incidents in the Correctional Unit. One of them in West Sumatra, where the Legal Aid Institute in Padang recorded three cases during the current year in 2019, occurred in Pariaman Class II-B of Correctional Institution. Similar incidents occurred in 2018 in which children in correctional institutions were recorded as experiencing physical, psychic, and sexual violence. The Indonesian Commission for the Protection of Children found that 26.8 percent of children in Special Children’s Prison were victims of violence in 2018. There has been widespread media coverage of officers’ violence and complex correctional problems in the last three years. Based on the literature study and unstructured interviews with correctional officers, several factors cause officers’ violence to prisoners. The following factors are the punitive attitude of correctional officers to prisoners and the lack of human rights knowledge, Standard Minimum Rules (SMR), and correctional officers’ correctional technicalities. In this study, the method used was descriptive qualitative research. Descriptive qualitative research is a form of research that includes a case study of an event. This study uses a qualitative method with a case study approach. Case studies are intended to test research questions and problems in which there is no separation of phenomena and context in the spectacle. This study explores the factors that trigger officers to commit violence against correctional inmates. Many things cause violent behavior, such as stress, psychic problems, and soon.